Kutubusittah dan Kutubutis’ah - Nuzurul Harmuliani; Rubino Rubino; Anjas Baik Putra (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
The purpose of this research is to find out the difference between kutubusittah and kutubutis'ah. Kutubusittah is the six books of hadith which are the master books of hadith, namely Sahih Bukhari, Sahih Muslim, Sunan Abu Dawud, Sunan At-Tarmizi, Sunan An-Nasa'I and Sunan Ibn Mazah, while kutubutis'ah is the six books of hadith in kutubusittah plus Al-Muwatha' by Imam Malik, These books are a form of the rapid development of hadith science in the third century hijriyah, with the existence of the kutubusittah and kutubutis'ah, the traditions are protected from false traditions and have been separated from da'if traditions. Based on the hard work and earnestness of the scholars of hadith during this period, books of hadith were published which contained authentic traditions and were protected from false traditions known as kutubusittah (six books) and kutubutis'ah (nine books) which can still be found today. Thus the third century Hijri was a golden age for the civilization of the Islamic world. Keywords: Kutubusittah, Kutubutis’ah